Camus and Aristotle on the Art Community and its Errors - Fendt, Gene (Labyrinth, 2020)
The purpose of this paper is to show the agreement of Camus and Aristotle on the cultural function of the art community (the community of artist and audience), in particular their criticism of what should be called barbarian or nihilistic practices of art. Camus' art and criticism have been frequent targets of modern critics, but his point is and would be that such critics have the wrong idea of the purpose of art. His answer to such critics and the parallelism of his ideas with Aristotle's criticism of barbarian culture, show that the real issue between Camus and his critics is cultural.